Trajectory of Indecision in College: An Illustration of Mixed Methods Research - Picard, France (Canadian Journal of Counselling and Psychotherapy, 2015)
This article focuses on the explanatory variables impacting the effectiveness of a transition program designed to reduce indecision among first-year college students in Québec. Mixed methods research was crucial in measuring exploratory variables such as the influence of student psychosocial characteristics and the college learning environment on the trajectory of indecision during the first semester. A repeated measures study involving 973 students was used. College professionals provided data into the learning environment and career guidance. The study presents new empirical evidence on the links between the career guidance and learning environment provided by colleges and the short-term trajectory of change in indecision.